Taxonomic notes on some Cheilostomata (Bryozoa) from Madeira - Berning, Björn (Zootaxa, 2012)
Five species of cheilostome Bryozoa from the Madeiran archipelago, which were all introduced during the late 19th andearly 20th centuries, are figured and redescribed following examination of the type specimens: Schizomavella noronhai(Norman), Saevitella peristomata (Waters), Phaeostachys schmitzi (Norman), Plesiocleidochasma porcellanum (Busk),and Stephanollona contracta (Waters). One species, previously recorded as Microporella decorata (Reuss), which is a fos-sil from the Miocene Paratethyan region nowadays placed in the genus Calloporina Neviani, is newly described as Cal-loporina mariae. The genus Schedocleidochasma Soule, Soule & Chaney is synonymised with Plesiocleidochasma Soule,Soule & Chaney, and the generic diagnoses of Calloporina Neviani, Saevitella Bobies and Plesiocleidochasma are amended.